OPTICAL COMPUTING: NEED AND CHALLENGE. - Abdeldayem, Hossin; Frazier, Donald O. (Communications of the ACM, 2007)
This article explores the concept and likelihood of an optical computer industry. Optical components have been successfully employed in CD-ROM drives, laser printers, Storage Area Networks (SANs), and biométrie devices at airports, but the author asserts optical computing has many advantages over electronic counterparts. Besides being immune to electromagnetic interference and free from electrical short circuits, optical materials are compact, lightweight, inexpensive to manufacture, possess superior storage density and parallel data processing is also less expensive than electronic. The challenges are that development of an optical computer would require coordination and funding of many interdisciplinary fields together with the will and vision to do so.